PRE-SERVICE SCIENCE TEACHERSâ READINESS TO INTEGRATE TECHNOLOGY (AN EXPLORATION TOWARD TPACK IN PRELIMINARY PRACTICAL CONTEXT) - Agustin, Rika Rafikah; Liliasari, Liliasari (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2016)
The purpose of this study was to capture pre-service science teachersâ Technological Pedagogical Content Knowledge (TPACK) that is demonstrated during preliminary practical context in term of peer teaching program- a course conducted prior to teaching practice. Ten pre-service science teachers were involved in a semester long peer teaching program. Descriptive method was employed with the use of teaching artifacts, observation and self-reported survey for representing the way the participant integrate technology into their teaching. TPACK constructs were defined using relevant literature as frameworks. This study found that TPACK ofÂ  pre-service science teachers were still low and is not sufficient for teaching science in junior high school. Furthermore, it is needed several supporting program to prepare pre-service science teachersâ competencies in teaching science with technology. In this case, more sophisticated peer teaching program with better purchase is necessity to improve TPACK competencies of pre-service science teachers.